2017
DOI: 10.1021/acs.jafc.7b01890
|View full text |Cite
|
Sign up to set email alerts
|

A Search for CD36 Ligands from Flavor Volatiles in Foods with an Aldehyde Moiety: Identification of Saturated Aliphatic Aldehydes with 9–16 Carbon Atoms as Potential Ligands of the Receptor

Abstract: Volatile compounds with an aldehyde moiety such as (Z)-9-octadecenal are potential ligands for cluster of differentiation 36 (CD36), a transmembrane receptor that has recently been shown to play a role in mammalian olfaction. In this study, by performing an assay using a peptide mimic of human CD36, we aimed to discover additional ligands for the receptor from volatiles containing a single aldehyde group commonly found in human foods. Straight-chain, saturated aliphatic aldehydes with 9-16 carbons exhibited CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 45 publications
3
16
0
Order By: Relevance
“…It was also found that oxGPC SRB species, like 1-(palmitoyl)-2-(5-keto-6-octenedioyl)phosphatidylcholine (KOdiA-PC, one of the most potent lipid ligands of CD36), inhibited the binding of fl-oxLDL to the CD36 peptides (16,30,31), confirming that the peptides bind oxLDL particles by recognising their oxGPC SRB moiety. A novel finding of our studies using the CD36 peptides was that aliphatic aldehydes such as tetradecanal, a distinct class of volatile odorants, were capable of inhibiting fl-oxLDL binding to the mimics (i.e., were identified as potential CD36 ligands) (32,33,35). Furthermore, others and we have discovered that CD36 is expressed by a population of olfactory sensory neurons and is abundantly present in the olfactory ciliary layer in mice (17,22,38).…”
Section: Preparation Of Mimic Peptides For Class B Scavengermentioning
confidence: 76%
See 4 more Smart Citations
“…It was also found that oxGPC SRB species, like 1-(palmitoyl)-2-(5-keto-6-octenedioyl)phosphatidylcholine (KOdiA-PC, one of the most potent lipid ligands of CD36), inhibited the binding of fl-oxLDL to the CD36 peptides (16,30,31), confirming that the peptides bind oxLDL particles by recognising their oxGPC SRB moiety. A novel finding of our studies using the CD36 peptides was that aliphatic aldehydes such as tetradecanal, a distinct class of volatile odorants, were capable of inhibiting fl-oxLDL binding to the mimics (i.e., were identified as potential CD36 ligands) (32,33,35). Furthermore, others and we have discovered that CD36 is expressed by a population of olfactory sensory neurons and is abundantly present in the olfactory ciliary layer in mice (17,22,38).…”
Section: Preparation Of Mimic Peptides For Class B Scavengermentioning
confidence: 76%
“…An oligopeptide containing amino acid residues 149-168 of human CD36 with biotin at the N-terminus was purchased from Life Technologies Japan (Tokyo), after synthesis (35). Peptides for SR-B1 [b5S-SRB1 187-206 , b5S-SRB1 187-206 (scramble) and b5S-SRB1 187-206 (3K/N)] were also purchased from the same vendor.…”
Section: Preparation Of Mimic Peptides For Class B Scavengermentioning
confidence: 99%
See 3 more Smart Citations